2000
DOI: 10.1002/1096-8644(200007)112:3<339::aid-ajpa5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Brachycephalization in Japan has ceased

Abstract: Somatometric data are presented which show that the rapid brachycephalization in Japan has recently ceased. The causes of brachycephalization are investigated in relation to the secular change in height. Increases in head breadth have been the main cause of brachycephalization, and its pattern of secular change is very similar to that in height. Associations between head breadth, height, and year of birth were examined by partial correlation coefficients and through a comparison of students and the general pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 25 publications
4
81
1
2
Order By: Relevance
“…Previous studies (Hossain et al, 2004(Hossain et al, , 2005 and others (Ohtsuki and Ito, 1980;Kouchi, 2000) showed that the association of head breadth (positive) and head length (negative) with the CI. Those results suggested that if head breadth Same notations as Table 2.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previous studies (Hossain et al, 2004(Hossain et al, , 2005 and others (Ohtsuki and Ito, 1980;Kouchi, 2000) showed that the association of head breadth (positive) and head length (negative) with the CI. Those results suggested that if head breadth Same notations as Table 2.…”
Section: Discussionmentioning
confidence: 87%
“…However, the present findings are based on female data. Previous studies (Kouchi, 2000;Hossain et al, 2004Hossain et al, , 2005 demonstrated that males and females showed the same tendency of brachycephalization/debrachycephalization in Japan and head breadth was positively associated with CI for both sexes. As far as we know there are no comparable studies available that document the relationship between the CI and craniofacial measurements; consequently, the present findings cannot be compared to other studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, our sample was not geographically diverse. The fact that increases in stature are correlated to brachycephalization in Japan but to dolichocephalization in Europe (Kouchi, 2000) suggests that the pattern of morphological variability of the modern human cranium may be affected by environmental factors. Including cranial specimens from different populations for analysis is a crucial issue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Three human crania with no documented population background, which were selected from medical education osteological collections, were medium-sized and had cephalic indices ranging from 0.7 to 0.8. The average modern Japanese would be the most circular (brachycephalic, 0.86) (Kouchi, 2000) amongst the variation of this index in our cranial database. The lowest index (0.20) was calculated for a giant anteater (DKY-2186).…”
Section: Contents Of Mcpa2mentioning
confidence: 90%